HRI usability evaluation of interaction modes for a teleoperated agricultural robotic sprayer. - Adamides, George; Katsanos, Christos; Parmet, Yisrael; Christou, Georgios; Xenos, Michalis; Hadzilacos, Thanasis; Edan, Yael (Applied Ergonomics, 2017)
Teleoperation of an agricultural robotic system requires effective and efficient human-robot interaction. This paper investigates the usability of different interaction modes for agricultural robot teleoperation. Specifically, we examined the overall influence of two types of output devices (PC screen, head mounted display), two types of peripheral vision support mechanisms (single view, multiple views), and two types of control input devices (PC keyboard, PS3 gamepad) on observed and perceived usability of a teleoperated agricultural sprayer. A modular user interface for teleoperating an agricultural robot sprayer was constructed and field-tested. Evaluation included eight interaction modes: the different combinations of the 3 factors. Thirty representative participants used each interaction mode to navigate the robot along a vineyard and spray grape clusters based on a 2 × 2 × 2 repeated measures experimental design. Objective metrics of the effectiveness and efficiency of the human-robot collaboration were collected. Participants also completed questionnaires related to their user experience with the system in each interaction mode. Results show that the most important factor for human-robot interface usability is the number and placement of views. The type of robot control input device was also a significant factor in certain dependents, whereas the effect of the screen output type was only significant on the participants' perceived workload index. Specific recommendations for mobile field robot teleoperation to improve HRI awareness for the agricultural spraying task are presented.